Optimisation of Air-water Harvester Machine Performance With Variations of Inlet Air Flow Velocities - Mirmanto, Mirmanto; Wirawan, Made; Tarmisi, Ahmad (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
In the dry season, some parts of Indonesia experience drought and clean water crisis which results in scarcity and difficulty in drinking water. One way to overcome this problem is to present a water-producing device from air called a water harvester machine. The purpose of this study was to examine the effect of the inlet air velocity of 4 m/s, 5 m/s, and 6 m/s on the mass of water produced and the rate of heat transfer. This study was conducted experimentally with R134a refrigerant working fluid, and a 1 PK rotary compressor and centrifugal fan. The results showed that the highest water mass, which was 5.99 kg, was obtained at an air velocity of 6 m/s. The highest heat transfer rate, which was 2080.2 W, was also obtained at a speed of 6 m/s. This can be caused by the high inlet air velocity, the inlet air mass flow rate is also high so that the water vapor content that enters is greater. As a result, the mass of water produced is greater and the rate of heat transfer that occurs is also greater.